Dynamic features of postnatal subventricular zone cell motility: a two-photon time-lapse study. - Nam, S; Kim, Y; Dryanovski, D; Walker, A; Goings, G; Woolfrey, K; Kang, S; Chu, C; Chenn, A; Erdelyi, F; Szabo, G; Hockberger, P; et al. (2007)
Neuroblasts migrate long distances in the postnatal subventricular zone (SVZ) and rostral migratory stream (RMS) to the olfactory bulbs. Many fundamental features of SVZ migration are still poorly understood, and we addressed several important questions using two-photon time-lapse microscopy of brain slices from postnatal and adult eGFP(+) transgenic mice. 1) Longitudinal arrays of neuroblasts, so-called chain migration, have never been dynamically visualized in situ. We found that neuroblasts expressing doublecortin-eGFP (Dcx-eGFP) and glutamic acid decarboxylase-eGFP (Gad-eGFP) remained within arrays, which maintained their shape for many hours, despite the fact that there was a wide variety of movement within arrays. 2) In the dorsal SVZ, neuroblasts migrated rostrocaudally as expected, but migration shifted to dorsoventral orientations throughout ventral regions of the lateral ventricle. 3) Whereas polarized bipolar morphology has been a gold standard for inferring migration in histologic sections, our data indicated that migratory morphology was not predictive of motility. 4) Is there local motility in addition to long distance migration? 5) How fast is SVZ migration? Unexpectedly, one-third of motile neuroblasts moved locally in complex exploratory patterns and at average speeds slower than long distance movement. 6) Finally, we tested, and disproved, the hypothesis that all motile cells in the SVZ express doublecortin, indicating that Dcx is not required for migration of all SVZ cell types. These data show that cell motility in the SVZ and RMS is far more complex then previously thought and involves multiple cell types, behaviors, speeds, and directions.